Pengalaman Orang Tua Bekerja dalam Pengasuhan Anak Usia 4–6 Tahun: Studi Fenomenologi di Kota Semarang - Coryza Nursyahbani; Muniroh Munawar; Dwi Prasetiyawati Diyah Hariyanti (JEA (Jurnal Edukasi AUD), 2026)
Parenting in early childhood plays a crucial role in children’s development during the golden period. However, the increasing number of working parents creates challenges in caregiving practices. This study aims to explore the lived experiences of working parents in raising young children and the meanings they attach to their caregiving roles. A qualitative approach with a phenomenological design was employed. Data were collected through in-depth, semi-structured interviews with three working parents who had children aged 4–6 years and were Interpretative Phenomenological Analysis. The findings indicate that working parents experience time constraints and role conflicts between professional and family responsibilities. Despite these challenges, they develop adaptive strategies to maintain the quality of parenting, particularly through meaningful emotional involvement with their children. Parenting is perceived as both an essential responsibility and a long-term investment in children’s development. The novelty of this study lies in revealing the lived experiences of working parents in balancing work and caregiving roles, as well as the adaptive strategies they employ to sustain emotional engagement with their children. This article contributes to the literature on early childhood parenting by emphasizing experiential perspectives and offers practical recommendations for parents, educators, and policymakers to support work–family balance.